2022
DOI: 10.1107/s2059798322007033
|View full text |Cite
|
Sign up to set email alerts
|

The crystal structure of CbpD clarifies substrate-specificity motifs in chitin-active lytic polysaccharide monooxygenases

Abstract: Pseudomonas aeruginosa secretes diverse proteins via its type 2 secretion system, including a 39 kDa chitin-binding protein, CbpD. CbpD has recently been shown to be a lytic polysaccharide monooxygenase active on chitin and to contribute substantially to virulence. To date, no structure of this virulence factor has been reported. Its first two domains are homologous to those found in the crystal structure of Vibrio cholerae GbpA, while the third domain is homologous to the NMR structure of the CBM73 domain of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 134 publications
2
7
0
Order By: Relevance
“…Currently, increasing LPMOs are found to have multiple conserved domains, which play an essential role in the substrate binding and catalytic efficiency of LPMOs ( Courtade and Aachmann, 2019 ; Mekasha et al, 2020 ). In addition, some domains may also protect LPMOs from autocatalytic inactivation ( Dade et al, 2022 ). The analysis of conserved domains showed that M2822 contained four conserved domains ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…Currently, increasing LPMOs are found to have multiple conserved domains, which play an essential role in the substrate binding and catalytic efficiency of LPMOs ( Courtade and Aachmann, 2019 ; Mekasha et al, 2020 ). In addition, some domains may also protect LPMOs from autocatalytic inactivation ( Dade et al, 2022 ). The analysis of conserved domains showed that M2822 contained four conserved domains ( Figure 3C ).…”
Section: Resultsmentioning
confidence: 99%
“…This observation agrees with the ~45-Å internal diameter of the XcpD N-module under closed conformation proposed by Douzi and colleagues ( 21 ). This is too narrow to accommodate the 55-Å-wide secreted effector CbpD ( 28 ) or the endopilus with an external diameter of at least 60 Å ( 29 , 30 ), but it is large enough to allow passive diffusion of bile salt molecules (~13 Å).…”
Section: Resultsmentioning
confidence: 99%
“…S3(b). From sequence analysis, the GbpA_2 domain of VhLPMO10A shares 66.0% and 30.6% sequence identity with those of VcLPMO10B (GbpA) and CbpD, respectively, while the module X domain shares 49.5% identity with that of VcLPMO10B (GbpA) and the fourth domain (CBM73) shares sequence identities of 66.67% and 47.1% with the two homologues (Wong et al, 2012;Dade et al, 2022). The structural comparison showed that the GbpA_2 domain of VhLPMO10A superimposes with those of VcLPMO10B (GbpA) and CbpD with r.m.s.d.s of 0.451 and 1.10 A ˚for 85 and 68 C atoms, respectively, while the module X domain of VhLPMO10A superimposes with that of VcLPMO10B (GbpA) with an r.m.s.d.…”
Section: Crystal Structures Of Apo and Copper-bound Vhlpmo10amentioning
confidence: 99%
“…The gbpA-encoded polypeptide was later characterized as having LPMO activity, which enables the bacterium to crack chitin layers into fragments by oxidative cleavage (Loose et al, 2014), producing more accession points for chitin hydrolysis by chitinases. Several gbpA gene homologues present in chitinolytic bacteria were later redesignated as AA10 LPMOs, one of which is CbpD from Pseudomonas aeruginosa, a chitin-oxidizing virulence factor containing three domains (an AA10 domain, a GbpA_2 domain and a CBM73 domain) that promotes the survival of the bacterium in human blood (Askarian et al, 2021;Dade et al, 2022). These AA10 LPMOs generally require a copper ion in the catalytic centre to support their catalytic activity.…”
Section: Introductionmentioning
confidence: 99%